FloRunTM ‘331’ Peanut Variety - Barry L. Tillman (EDIS)
FloRunTM ‘331’ peanut variety was developed by the University of Florida, Institute of Food and Agricultural Sciences, North Florida Research and Education Center near Marianna, Florida.  It was released in 2016 because it combines high yield potential with excellent disease tolerance. FloRunTM ‘331’ has a typical runner growth habit with a semi-prominent central stem and medium green foliage.  It has medium runner seed size with high oleic oil chemistry.